Multimedia tool for basic literacy: Adopting applied phonetics - Azman, Farah Nadia; Dolhalit, Mohamad Lutfi; Shahbodin, Faaizah (2010)
In Malaysia, a child is expected to be able to read by the age 7 before they entered formal schooling system. This shows that an effective teaching and learning method should be taken in coaching basic reading skills conducted in preschool. Some method has been implemented incorporate multimedia approach in teaching reading. While this is a good achievement, an e-learning environment will not be successful without a meaningful instruction. A principled method should be identified in developing an interactive educational multimedia tool in assisting students to read. In this paper, the phonetic approach is proposed in teaching reading skills presented with the power effect of multimedia and efficient instructional design. We first observe printed media sold nationwide that apply phonetic approach. We then borrow the basic ideas from the observed materials and classify lists of content equivalence. If applied phonetics are understood and used effectively, an immediate impact could be achieved in using multimedia assisted learning in classroom environment.